The Influence of Organizational Citizenship Behavior and Work-Life Balance on Organizational Commitment: (A Study on e-Fishery Employees) - Suratman, Maman; Firdaus, Zulfikry (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2025)
This research focuses on eFishery, a start-up company based in Bandung, specifically during the period of December 2024 to January 2025. During this time, the start-up underwent a significant layoff, impacting nearly 95% of its employees, due to issues of fraud. This crisis provides a compelling case study for examining employee retention strategies from a Human Resource Management (HRM) perspective. The study aims to investigate the influence of Organizational Citizenship Behavior and Work-Life Balance on Organizational Commitment among eFishery employees. A quantitative causal associative research method was employed, with the population comprising eFishery employees during the December 2024 – January 2025 period. Three Likert scales were utilized to measure the variables: the Organizational Citizenship Behavior Scale, the Work-life Balance Scale, and the Organizational Commitment Scale. Multiple linear regression analysis was used for data analysis. Empirical research findings indicate that employee Organizational Citizenship Behavior at eFishery is at a moderate level, while Work-Life Balance and Organizational Commitment are high. The results demonstrate a significant positive influence of Organizational Citizenship Behavior on Organizational Commitment, a significant positive influence of Work-life Balance on Organizational Commitment, and a significant combined influence of Organizational Citizenship Behavior and Work-life Balance on Organizational Commitment.